Is 3D-CT reformation using free software applicable to diagnosis of bone changes in mandibular condyles? - Marília Gerhardt de Oliveira; Luciano Engelmann Morais; Daniela Nascimento Silva; Helena Willhelm de Oliveira; Cláiton Heitz; Lêonilson Gaião (University of São Paulo, 2009)
OBJECTIVES: This study evaluated the agreement of computed tomography (CT) imaging using 3D reformations (3DR) with shaded surface display (SSD) and maximum intensity projection (MIP) in the diagnosis of bone changes in mandibular condyles of patients with rheumatoid arthritis (RA), and compared findings with multiplanar reformation (MPR) images, used as the criterion standard. MATERIAL AND METHODS: Axial CT images of 44 temporomandibular joints (TMJs) of 22 patients with RA were used. Images were recorded in DICOM format and assessed using free software (ImageJ). Each sample had its 3DR-SSD and 3DR-MIP results compared in pairs with the MPR results. RESULTS: Slight agreement (k = 0.0374) was found in almost all comparisons. The level of agreement showed that 3DR-SSD and 3DR-MIP yielded a number of false-negative results that was statistically significant when compared with MPR. CONCLUSIONS: 3DR-SSD or 3DR-MIP should only be used as adjuvant techniques to MPR in the diagnosis of bone changes in mandibular condyles.